IbM KELOMPOK USAHA BERSAMA (KUB) SULAM PITA DI KOTA SEMARANG - Fatmasari Sukesti; Triyono Triyono; Musdalifah Musdalifah; Alwiyah Alwiyah (Universitas Muhammadiyah Semarang, 2017)
The products of ribbon embroidery became a popular trend since five years ago. With the development of beautiful design and embroidered motifs, various embroidered ribbon products can be produced and become a promising business opportunity. Joint Business Group (KUB)